1987
DOI: 10.1177/000348948709600301
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography of the Ethmoid Labyrinth and Adjacent Structures

Abstract: The architecture of ethmoid labyrinths as well as their relationships with adjacent structures are reviewed, giving special emphasis to the anatomic variants common in this area. The study was performed on six young normal subjects who were submitted to high resolution computed tomography. Approximately 25 axial scans, parallel to the floor of the anterior cranial fossa, were performed on each subject; four to five coronal CT scans were also added. Further data were supplemented by examinations of 62 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Likewise, this high prevalence may be explained by the criteria we used to define protrusion and dehiscence. However, previous studies reported a wide range of protrusion rates of 8 to 70% [31, 32]. Fuji et al found that 4% of optic nerves were dehiscent of bone in the lateral sphenoid [26].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, this high prevalence may be explained by the criteria we used to define protrusion and dehiscence. However, previous studies reported a wide range of protrusion rates of 8 to 70% [31, 32]. Fuji et al found that 4% of optic nerves were dehiscent of bone in the lateral sphenoid [26].…”
Section: Discussionmentioning
confidence: 99%
“…The pneumatization can extend into the greater wing of sphenoid, pterygoid process, clivus, and sometimes into the anterior clinoid process. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…In 1987, Teatini et al (11) showed a small gap in LP with no fat entrapment. Chow and Mafee (12) reported prolapse of medial rectus into the ethmoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Being aware of the dehiscence of LP is crucial before sinus surgery, since misdiagnosis may make perforation of orbital wall and damage the medial rectus and superior oblique hematoma and ocular infections (11,14).…”
Section: Discussionmentioning
confidence: 99%